Pengaruh Jenis Bahan Bakar Limbah Terhadap Unjuk Kerja Kompor Burner Spiral Pada Proses Pirolisis Biomassa: Indonesia - Bambang Surono; Juni Ismanto; Kemas Ridhuan (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2024)
ABSTRACT Waste fuel is the leftover fuel from a business or activity that can damage the environment. Therefore, waste fuel must be able to be used as reusable energy, such as stove fuel for the biomass pyrolysis combustion process. The purpose of this study is to determine the effect of fuel type on charcoal and liquid smoke yield, temperature, combustion time, and flame in spiral burner stoves and pyrolysis reactors. This research method uses quantitative with experimental data collection techniques. The biomass pyrolysis raw materials used are rubber wood biomass with a capacity of 8 kg that has been dried, while the variations of spiral burner stove fuel used are diesel, used oil, and used cooking oil. From the results of the study, the type of fuel affects the yield of charcoal and liquid smoke. Where the most charcoal results in various types of diesel fuel are 4 kg, but the results of liquid smoke obtained are at least 1,850 ml. Furthermore, in the variation of used fuel oil, charcoal results of 3.8 kg and liquid smoke results of 1,900 ml. Then the variation of used cooking oil fuel gets the lowest charcoal yield of 3.51 kg, but the most liquid smoke obtained is 2,050 ml. In the variety of diesel fuel, the highest temperature of the burner flame is 1,018 oC and the temperature inside the reactor is 238.3 oC with a pyrolysis process time of 300 minutes and has the largest flame. In the spent fuel oil variation, the highest temperature of the burner flame is 988.1 oC and the temperature inside the reactor is 232.9 oC with a pyrolysis time of 330 minutes. While in the variation of used cooking oil fuel, the highest temperature of the burner flame is 984 oC and the temperature inside the reactor is 234.8 oC with a combustion time of 340 minutes and the flame produced is the smallest. Keywords : Pyrolysis, Spiral Burner Stove, Waste Oil, Used Cooking Oil, Rubber Wood, Liquid Waste.